If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + 7(3 + -4k) = 31 2 + (3 * 7 + -4k * 7) = 31 2 + (21 + -28k) = 31 Combine like terms: 2 + 21 = 23 23 + -28k = 31 Solving 23 + -28k = 31 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-23' to each side of the equation. 23 + -23 + -28k = 31 + -23 Combine like terms: 23 + -23 = 0 0 + -28k = 31 + -23 -28k = 31 + -23 Combine like terms: 31 + -23 = 8 -28k = 8 Divide each side by '-28'. k = -0.2857142857 Simplifying k = -0.2857142857
| 5m^2+m/7m | | 4(v+5)=-8 | | 7b(-6b-4)= | | 3d+16=d+18 | | 4/x-1/2x=-7/4 | | -4/7(x1/4)=3/7 | | 38=20+3p | | 4/b-1/2b=-7/4 | | a+5=19 | | -68+-17= | | 3/5q-7/5=2q | | 2.4x+5.6=11.2 | | 7-5y=34 | | 14m+26=0 | | 0=14m+26 | | Y=3(3y-1)-13 | | 26+8= | | (4+3i)/(5-2i) | | 3.4d-1.7=6.8 | | 3z+6z=60-1z | | 4+3i/5-2i | | 40p+7(1.5)p=489.85 | | 4p^2+4p-48=0 | | 6(4b-5)=23 | | (4w+3)(8+w)=0 | | 2(4t-2)+t=16t | | ((2/x)+3)=((5x-7)/x) | | 6(y-1)+5y-6=65 | | X^2+9x+6/(x+6) | | x^2+(7/2)x-2 | | 8c-3=5 | | 4+2h=10 |